Temporal variation characteristics and source apportionment of metal elements in PM2.5 in urban Beijing during 2018–2019. (1st January 2021) - Zhao, Shuang; Tian, Hezhong; Luo, Lining; Liu, Huanjia; Wu, Bobo; Liu, Shuhan; Bai, Xiaoxuan; Liu, Wei; Liu, Xiangyang; Wu, Yiming; Lin, Shumin; Guo, Zhihui; et al.
Abstract: To explore high-resolution temporal variation characteristics of atmospheric metal elements concentration and more accurate pollution sources apportionment, online monitoring of metal elements in PM2.5 with 1-h time resolution was conducted in Beijing from August 22, 2018 to August 21, 2019. Concentration of 18 elements varied between detection limit (ranging from 0.1 to 100 ng/m 3 ) and nearly 25 μg/m 3 . Si, Fe, Ca, K and Al represented major elements and accounted for 93.47% of total concentration during the study period. Compared with previous studies, airborne metal pollution in Beijing has improved significantly which thanks to strict comprehensive control measures under the Clean Air Action Plan since 2013. Almost all elements present higher concentrations on weekdays than weekends, while concentrations of elements associated with dust sources during holidays are higher than those in working days after the morning peak, and there is almost no concentration difference in the evening peak period. Soil and dust, vehicle non-exhaust emissions, biomass, industrial processes and fuel combustion were apportioned as main sources of atmospheric metal pollution, accounting for 63.6%, 18.4%, 16.8%, 1.0% and 0.18%, respectively. Furthermore, main occurrence season of metal pollution is judged by characteristic radar chart of varied metal elements proposed for the first time in this study, for example, fuel combustion type pollution mainly occurs in winter and spring. Results of 72-h backward trajectory analysis of air masses showed that, except for local emissions, atmospheric metal pollution in Beijing is also affected by regional transport from Inner Mongolia, Hebei, the Bohai Sea and Heilongjiang. Graphical abstract: Image 1 Highlights: Content of 18 metals in PM2.5 of Beijing with 1-h resolution for 1 year is gained. Higher concentrations of metal elements are observed during weekdays than weekends. K concentration in Beijing shows an order of winter > autumn > spring ≫ summer. Soil and dust are identified as predominate source of metal elements in PM2.5 . Radar chart of metal elements is used for the first time to discern pollution type. Abstract : Temporal variations and source apportionment of metals are presented based on 1-h time resolution monitoring of metal elements in PM2.5 in Beijing from August 22, 2018 to August 21, 2019.